A Kind of Decision Model Research Based on Big Data and Blockchain in eHealth - Wang, Xiaohuan; Hu, Qingcheng; Zhang, Yong; Zhang, Guigang; Juan, Wan; Xing, Chunxiao (Web Information Systems and Applications, 2018)
Big Data is known as the ability of solving data sources, improving productions, and analyzing problems more faster and effectively. Blockchain is good at solving the problems of data security, sharing and reconciliation. In this paper, we introduce how to use the Big Data and Blockchain to change the strategies of decision model. We take the application of medical and health industry for example, recommend the precision analysis technology based on the Big Data and Blockchain, adopt the closed loop analysis and feedback mechanism, establish an intelligent contract system, use the weighted decision model to implement the decision-making process effectively.